2009
DOI: 10.1007/s11172-009-0149-5
|View full text |Cite
|
Sign up to set email alerts
|

New C70(CF3) n isomers (n = 12, 14, 16). Realkylation and addend rearrangements

Abstract: New isomers of trifluoromethyl derivatives of [70]fullerene, C 70 (CF 3 ) 12 (one isomer), C 70 (CF 3 ) 14 (three isomers), and C 70 (CF 3 ) 16 (one isomer) were synthesized, chromatographi cally isolated, and characterized by single crystal X ray analysis. Three of the five new isomers were obtained by annealing a mixture of higher trifluoromethyl derivatives (realkylation*). Trifluoromethylation of two individual C 70 (CF 3 ) 12 isomers revealed rearrangements of CF 3 groups on the fullerene sphere along wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
31
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 19 publications
1
31
0
Order By: Relevance
“…Compound 84 ( 10 , all ten groups are placed mirror symmetrically at para positions in adja cent six membered rings, forming a continuous chain (see Thus, all the cage pentagons each have one added CF 3 group. Two almost isolated benzenoid rings stabilize the structure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compound 84 ( 10 , all ten groups are placed mirror symmetrically at para positions in adja cent six membered rings, forming a continuous chain (see Thus, all the cage pentagons each have one added CF 3 group. Two almost isolated benzenoid rings stabilize the structure.…”
Section: Resultsmentioning
confidence: 99%
“…The compounds of the formulas C 84 (16)(CF 3 ) 2m (2m = 8, 10,12,14,18) and C 84 (18)(CF 3 ) 2m (2m = 10, 12) were isolated and characterized by X ray diffraction method for the first time. The basic principles of seccessive trifluoromethylation of C 84 (16) and C 84 (18) isomers in a wider range of compositions were found based on the experimental data obtained and results of quantum chemical calculations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…From certain fractions, crystalline sub stances were obtained by slow evaporation of the solvent. According to X ray diffraction analysis, the fractions with retention times 8.41 and 14.78 min (toluene : hexane =3 : 2, 4.6 mL min -1 ) and with retention times 8 [5,6] fullerene (C 60 (C 4 F 8 ) 6 I) and C 60 (C 4 F 8 ) 2 I. 10 Therefore, these compounds are the reaction products in both the C 60 -C 2 F 4 I 2 and C 60 -C 4 F 8 I 2 system.…”
Section: Resultsmentioning
confidence: 99%
“…The chromatographic analysis in combination with mass spectrometry (MALDI) showed that compounds C 60 (C 4 F 8 ) 5 were also present among the reaction prod ucts, but their structures are unknown yet. Since the con tent of these compounds in the reaction products was very small, we could not isolate them in sufficient amounts, hence, we could not obtain the crystals for X ray diffrac tion analysis.…”
Section: Resultsmentioning
confidence: 99%